Respuesta :
Okay so first you need to put it into point slope form which is y - y1=m(x-x1)
So y + 3 = 3 ( x - 0)
y+3 = 3x - 0
then carry the 3 over.
y= 3x - 0 - 3
y= 3x -3 is your answer.
So y + 3 = 3 ( x - 0)
y+3 = 3x - 0
then carry the 3 over.
y= 3x - 0 - 3
y= 3x -3 is your answer.
y=mx+b
m=slope
b=y intercept (take the point and take the y value and input it for b)
crosses y axis=y intercept=(0,-3), b=-3
slope=3
y=3x-3
m=slope
b=y intercept (take the point and take the y value and input it for b)
crosses y axis=y intercept=(0,-3), b=-3
slope=3
y=3x-3